Evaluation of galectin‐3, peptidylarginine deiminase‐4, and tumor necrosis factor‐α levels in gingival crevicular fluid for periodontal health, gingivitis, and Stage III Grade C periodontitis: A pilot study. Issue 1 (10th May 2021) - Akkaya, Hazal Üstünel; Yılmaz, Huriye Erbak; Narin, Figen; Sağlam, Mehmet
Abstract: Background: Comparing the gingival crevicular fluid (GCF) levels of galectin‐3, peptidylarginine deiminase 4 (PAD4) and tumor necrosis factor‐alpha (TNF‐α) in individuals with stage III grade C periodontitis and gingivitis and with healthy periodontium was the purpose of this clinical research. Methods: Sixty systemically healthy and non‐smoker individuals consisting of stage III grade C periodontitis (group S3P/n = 20), gingivitis (group G/n = 20), and periodontally healthy (group HP/n = 20) were recruited for this research. Clinical parameters such as probing depth, clinical attachment level, gingival index, plaque index, and bleeding on probing were recorded in periodontal charts. Enzyme‐linked immunosorbent assay method was used in evaluating the GCF levels of galectin‐3, PAD4, and TNF‐α for study groups. Results: The GCF galectin‐3 total amount was highest in group S3P compared with group G and group HP ( P  <0.05). Its total amount was also higher in group G compared with group HP ( P  <0.05). The GCF PAD4 total amount was higher in group S3P compared with group HP ( P  <0.05) but was similar with group G ( P >0.05). Its total amounts were also similar in group G and group HP ( P >0.05). The GCF TNF‐α total amounts were similar in group S3P and group G ( P >0.05) but significantly greater than the group HP ( P ˂0.05). The GCF galectin‐3, PAD4, and TNF‐α concentrations were lower in the group S3P and group G compared with the group HP ( P  <0.05). There were significant positive correlations between GCF galectin‐3 total amount and all clinical parameters ( P ˂0.01) and also between GCF galectin‐3 and TNF‐α total amounts ( P ˂0.01). There was no correlation between PAD4 and clinical parameters, or between PAD4 and TNF‐α ( P >0.05). Conclusions: Galectin‐3 and PAD4 may be involved in the periodontal disease pathogenesis considering the elevated levels of these molecules in periodontal disease. These biomarkers may be used in the diagnosis of periodontal diseases.